STUDI ORGANOLOGI ALAT MUSIK TAR PADA MASYARAKAT MELAYU DI DESA PUNGGUR KECIL KECAMATAN SUNGAI KAKAP KABUPATEN KUBU RAYA - Yahya, Akhmed; Fretisari, Imma; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe writing of the instrument of tar manu facturing process, especially the problem on this research that is the structur of the instrument of tar, and how the manufacturung process of the instrument of tar. The method in this research is a descriptive method with qualitative form of research is Tajudin Bin Abdul, Rusmandel, and Anwar Dja’far. Data validty cheking in this resach is observation exixtension and triangulition technique. This research’s results to describing the instrument of tar structur, manufacturing proses, and how to play the instrumen of tar in the Malay Society in Desa Punggur, Kecamatan Sungai Kakap, Kabupaten Kubu Raya, by Tajudin Bin Abdul Hamid. Keywords: Study organologi, Instrument of tar in the Malay Society